The Influence of Product Differentiation and Reference Groups on Xiaomi Smartphone Purchasing Decisions - Yoanita Sherly Owenda; Joko Samboro (Jurnal Impresi Indonesia, 2024)
Various smartphone brands with varying prices and specifications continue to emerge and develop in society. This study aims to determine the effect caused by product differentiation and reference groups on consumer purchasing decisions. This research is a quantitative research with product differentiation and reference groups as independent variables and consumer purchasing decisions as dependent variables. This study uses questionnaire data collection techniques and obtained 68 respondents, namely students of D-IV Marketing Management Study Department of Business Administration Malang State Polytechnic who use Xiaomi smartphones. Data analysis used was multiple linear regressions. The results show that partially product differentiation variables have a positive and significant effect on purchasing decisions, besides that the reference group variables also have a positive and significant effect on purchasing decisions. So from that it can be concluded that differentiation and reference groups can influence consumer purchasing decisions by increasing the superiority and value of the product and increasing the company's image to attract consumer attention.